Graphene Wrapped FeSe2 Nano‐Microspheres with High Pseudocapacitive Contribution for Enhanced Na‐Ion Storage. Issue 18 (12th March 2019) - An, Changsheng; Yuan, Yifei; Zhang, Bao; Tang, Linbo; Xiao, Bin; He, Zhenjiang; Zheng, Junchao; Lu, Jun
Abstract: Pseudocapacitance is a Faradaic process that involves surface or near surface redox reactions. Increasing the pseudocapacitive contribution is one of the most effective means to improve the rate performance of electrode materials. In this study, graphene oxide is used as a template to in situ synthesize burr globule‐like FeSe2 /graphene hybrid (B‐FeSe2 /G) using a facile one‐step hydrothermal method. Structural characterization demonstrates that graphene layers not only wrap the surfaces of FeSe2 particles, but also stretch into the interior of these particles, as a result of which the unique nano‐microsphere structure is successfully established. When serving as anode material for Na‐ion batteries, B‐FeSe2 /G hybrid displays high electrochemical performance in the voltage range of 0.5–2.9 V. The B‐FeSe2 /G hybrid has high reversible capacity of 521.6 mAh·g −1 at 1.0 A g −1 . Meanwhile, after 400 cycles, high discharge capacity of 496.3 mAh g −1 is obtained at a rate of 2.5 A g −1, with a high columbic efficiency of 96.6% and less than 1.0% loss of discharge capacity. Even at the ultrahigh rate of 10 A g −1, a specific capacity of 316.8 mAh g −1 can be achieved. Kinetic analyses reveal that the excellent performance of the B‐FeSe2 /G hybrid is largely attributed to the high pseudocapacitive contribution induced by the special nano‐micro structure. Abstract : Graphene oxide is used as a template to in situ synthesize burr globule‐like FeSe2 /graphene hybrids using a facile one‐step hydrothermal method. The unique structure can improve the pseudocapacitive contribution (90.5% at 1.0 mV s −1 ), responsible for the superior rate capability. Meanwhile, the graphene matrix serves as a conducting 3D network, is beneficial to the electronic conductivity and suppresses the volume change.